Anaesthesia for open abdominal aortic surgery. Issue 5 (May 2019) - Duncan, Alastair; Pichel, Adam
Abstract: The prevalence of abdominal aortic aneurysm (AAA) and the number of patients undergoing aneurysm repair is increasing. The UK has worked tirelessly to reduce its operative mortality rates for elective open AAA repair with the introduction of a quality improvement programme. Reducing death from ruptured aortic aneurysm has been the focus of the national screening programme. Despite the increased prevalence of disease and intervention, the popularity of open repair has diminished since the advent of endovascular repair (EVAR). The short-term benefits of EVAR when compared to open repair are well described; however, the long-term survival benefits, freedom form re-intervention and cost effectiveness of EVAR are not proven. The choice of technique for emergency AAA repair is contentious, with the more traditional approach of open repair being rapidly overtaken by endovascular options. In this article we provide an overview of the evidence supporting the different treatment options, outline current approaches to risk stratification, describe the key physiological changes that occur during open repair and describe an overview of the approach to perioperative management.